Receding‐horizon OPF for real‐time management of distribution networks. Issue 9 (14th March 2018) - Robertson, James; Harrison, Gareth; Wallace, Robin
Abstract : This study presents a new formulation for real‐time active network management (ANM) control of distribution networks to maximise energy yield from distributed generation (DG). Coordinated scheduling of renewable DG and distribution network control assets can limit DG curtailment and significantly increase energy yield and economic performance of DG in weak or congested networks. Optimal power flow (OPF) has been employed in the literature for this purpose. However, single time frame snapshot formulations are limited by their narrow interpretation of temporal constraints. Here a formulation is presented for a new receding‐horizon OPF technique to better control real‐time ANM in distribution networks with high levels of temporally and spatially variable renewable DG. It is shown to improve the coordination between time sequences of system dispatch and improve voltage performance.